Enforcement Of Administrative Immigration Laws Legal Study On Immigration Laws Towards Foreign Citizens In Indonesia (Analysis Of Deportation Cases) - Mohamad Teguh Yudi; Yusup Hidayat; Suartini Suartini (Green Publisher Indonesia, 2024)
The deportation of foreigners for committed violations is considered as the last resort taken by the state to address foreign nationals who are believed to disrupt public order, endanger public safety, or refuse to comply with applicable laws and regulations. The research problem formulation is how the implementation of deportation according to Immigration Law Number 6 of 2011 and the analysis of the case. The research method applies a normative juridical method with a conceptual approach. The results of this study indicate that the implementation of deportation as a response to immigration law violations is regulated in Law Number 6 of 2011. This is a law enforcement measure to expel foreign nationals who have violated the law, as an effort to maintain state sovereignty.